(untitled) (Al-Academy, 2023)
The philosophies don’t forgets the subject silence because it effecting in life human , the kinds artist don’t lost the silence , exactly the theatrical arts because if the actor don’t the select silence he is don’t effect in the audience , this study giving the important for active the select silence in Iraqis theatre , so this search composed of : the preface that composed of : the search problem , and important the search and need it , aimed the search , lines search it composed of the lines time , lines place , and lines subject , and the terms limited . the theatrical line that composed The second topic the first topic the silence in the philosophers, part , active the select silence in the theatre text. The Third topic active the select silence in acting the actor in the world . the measures that composed of analyse Romelos Theater and comedy seven days. the results composed of :-1- The selective silence of the emperor, his wife, and the vizier in the play Romilos had an effect on setting the rhythm of the theater . 2-the selective silence in play Romilos Help achieve The correct timing in the entry of the antique seller on the emperor . 3- the selective silence Responsible for achieving emotional memory, especially in the last scene of the emperor 4- The complete selective silence of the grandfather, his granddaughter and the stranger in the seven days Contribute to the development of the actor’s presence and influence on the recipient . 5- The complete selective silence of the grandfather, his granddaughter and the stranger in the seven days help the actor Help the actor relax . 6- the selective silence After the funeral music in which he participated which he participated in the grandfather, his granddaughter and the stranger in the seven days that important for the actor on movement and diction. the conclusions ended this search with important dictionaries and the sources and the abstract